Studi Ekologi Tumbuhan Paku (Pteridophyta) di Taman Wisata Alam Danau Sicike-Cike dan Hutan Desa Serdang Sumatera Utara - Devi Adriati; Melfa Aisyah Hutasuhut (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the diversity, evenness, and distribution patterns of ferns as indicators of ecosystem quality and environmental changes. The method used is an exploratory survey with quadrat plots arranged using purposive sampling. Each study site consists of 24 plots measuring 5 x 5 m, positioned opposite each other. The results showed that 44 species of ferns from 20 families were found in both locations. The most frequently found species in the Sicike-cike Lake Nature Tourism Park was Phymatopteris triloba (Hountt) Copel., while in the Serdang village forest, it was Hymenophyllum sp. Canonical correspondence analysis indicated that the presence of ferns in both locations was influenced by temperature, humidity, light intensity, and altitude. Keywords: Ferns, Diversity, Evenness, Distribution Pattern, Canonical